Bubble departure characteristics in nanofluid flow boiling - Patra N.; Gupta V.; Ghosh P.; Singh R.S. (My University, 2025)
This paper presents the results of visualization experiments that were carried out conducted to investigate the bubble departure characteristics in flow boiling of water and dilute oxide- based nanofluids. The experiments were performed under the atmospheric pressure, and liquid subcooling was around 20 K. In the experiments, bubbles were generated on a the vertical surface of a stainless steel rod containing a cartridge heater under subcooled as well as nearly saturated conditions. Bubble images were captured with a Mikrotron Motion BLITZ Cube 4 high-speed video camera. Images were analyzed with the purpose of finding bubble departure characteristics such as, i.e., bubble diameter and bubble departure frequency using ImageJ, image-processing software. Addition of nanoparticles into the base fluid decreases bubble diameter and increases the bubble departure frequency. Bubble diameter and bubble frequency increase in both water and nanofluids with increase in applied heat flux. © 2019 by Begell House, Inc.